PERENCANAAN DINDING PENAHAN TANAH UNTUK MENANGGULANGI KELONGSORAN PADA RUAS JALAN HUTUMURI KECAMATAN LEITIMUR SELATAN - Soumahu, Valentino; Lewakabessy, Godfried; Latar, Sjafrudin (Journal Agregate, 2023)
Retaining walls serve the purpose of withstanding lateral pressure from the soil behind them. This construction can be considered as an alternative for addressing potential landslides along the embankment of Hutumuri village road. The aim of this research is to plan a retaining wall as one of the reinforcement alternatives for the embankment along the section of Hutumuri road from Station (STA) 1+200 to 1+270. The planning of the retaining wall along this road section begins with a soil stability analysis using the simple slice method. Subsequently, employing the Terzaghi method, the stability of the wall against soil pressure behind it is analyzed to prevent displacement and potential collapse during the construction of the retaining wall. Utilizing the Simple Slice method and Rankine's theory to assess the slope conditions and the construction of the retaining wall along Hutumuri road section, values for the slope safety factor are obtained. In the unsafe condition, the slope safety factor is less than 1.2, indicating the need for an alternative slope reinforcement, such as a retaining wall. The analysis results for the stability of the Counterfort-type retaining wall indicate that it does not meet the requirements. This is due to the fact that, in section I, the soil bearing capacity safety factor (FS) is 2.454, where the value of FS is less than the recommended value of 3, signaling the need for further consideration and potential adjustments in the design.